Perkembangan Penelitian Hubungan Industrial, Dialog Sosial, dan Peran Pemerintah Daerah: Analisis Bibliometrik dan Agenda Penelitian Masa Depan - Kurniawan, Moh Arief; Saluy, Ahmad Badawi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Industrial relations face increasingly complex challenges due to changing employment patterns, regulatory dynamics, and the increasing need for effective social dialogue mechanisms to maintain stable employment relations. Although studies on industrial relations continue to develop, comprehensive mapping of the relationship between social dialogue, government intervention, and industrial relations stability remains limited. This study aims to analyze the development of research themes, identify publication trends, and identify research gaps regarding the relationship between social dialogue, government intervention, and industrial relations stability through a Systematic Literature Review (SLR) approach. Data were obtained from the Scopus database with a publication range of 2015–2025. Literature selection was carried out using the PRISMA stages, which include identification, screening, eligibility assessment, and inclusion, resulting in 20 articles meeting the analysis criteria. Furthermore, bibliometric mapping was conducted using VOSviewer. The results show that collective bargaining (23 occurrences), industrial relations (15 occurrences), and trade unions (11 occurrences) are the most dominant themes, while studies on local government are still relatively limited (4 occurrences). These findings indicate an opportunity for research development on the role of local governments in strengthening social dialogue and supporting the creation of adaptive and sustainable industrial relations.